Learning from Malaysia: Oil Palm’s Empty Bunches for Biological Adsorbent in Diesel Oil Spill Disasters - Ronald Ronald; Raldi Hendro Koestoer (Indonesian Journal of Earth Sciences, 2022)
The oil spill disaster potentially occurance is an inseparable part of oil, gas exploration and transportation activities that are national and international concern. Oil palm’s empty bunches are a non-toxic material that is cheap, renewable, and widely found in Indonesia as one of the world's palm oil producing countries and can be used to deal with environmental pollution. Research that has been conducted in Malaysia has found that the fiber of eoil palm’s mpty bunches has good absorption in diesel oil spills. This writing method is with literatur review and compares the conditions in Malaysia with Indonesia. This paper aims to provide a comparison of the utilization and use of oil palm’s empty bunches for the benefit of handling oil spills in the waters. In conclusion, Malaysia is more advanced in conducting research and utilizing oil palm’s for adsorbent to spills that can also be done in Indonesia.